Metadata and its applications in the digital library : - Liu, Jia (Libraries Unlimited, 2007)
Metadata is everywhere, especially if you class the Internet in that "everywhere." However, the standards and practices of metadata are more closely aligned with electronic publishing and digital libraries. Liu starts with the notion that not everyone knows what metadata is or what it does, so she begins by defining it and its types and its encoding standards. She then turns to specific projects and their applications in the digital library, including BIBLINK, the MetaLib Project and the Nordic Metadata Project, as well as metadata applications in the digital library such as PANDORA, the Oxford Digital Library, DSpace Metadata and as used in the Peking U. Rare Book Digital Library. (booknews.com)